The use of learner reading aloud in the English lesson: a look at the micro and macro levels of oral reading - Huszti Ilona; Густі Ілона (PoliPrint Kft., 2009)
A jelen kötet egy nyelvpedagógiai kutatást mutat be részletesen, mely hét kárpátaljai magyar iskolában folyt. A szerző a kutatást azzal a céllal végezte, hogy felmérje, hogyan olvasnak angolul a tizenkét éves tanulók. Az eredmények azt bizonyítják, hogy a hatodikosok szinte csak hangosan olvasnak az angolórán, ami viszont leginkább gátolja a tanulók szövegértését. A kötet végén a szerző javaslatok fogalmaz meg a tanárok számára a hangos olvasással mint tantermi eljárással kapcsolatban, illetve további kutatási irányokat jelöl meg a nyelvpedagógiai szakma számára.

Резюме. У роботі розглянуто тему з методики викладання англійської мови: використання техніки читання вголос. Книга описує дослідження, що авторка посібнику провела серед учнів 6-го класу закарпатських шкіл з угорською мовою навчання. Метою дослідження була зрозуміти причини, з яких вчителі англійської мови використовують техніку читання вголос на уроках англійської мови, а також проаналізувати помилки, що учні роблять в процесі читання вголос. У книзі говориться про взаємозв’язок читання вголос і зрозуміння прочитаного тексту учнями, роль вчителя при виправленні помилок учнів. Подані загальні висновки та педагогічні й дослідницькі імплікації, що були сформовані на результатах даного емпіричного дослідження. Посібник рекомендується викладачам методики, молодим науковцям, аспірантам, здобувачам наукових ступенів, студентам філологічних спеціальностей вищих навчальних закладів, а також вчителям, які викладають англійську мову в школі.

Abstract. In Transcarpathian Hungarian schools, it is common practice among English teachers to apply the technique of learner reading aloud in the English lessons (Huszti, 2002, 2003a, 2003b). Some researchers (e.g. Helgesen and Gakuin, 1993) are against the use of this technique in its ‘traditional way’ (see Section 3.3), but their claim is not grounded on any empirical research findings. Because the traditional learner oral reading is a widely applied technique in the lessons of English in Transcarpathian Hungarian schools, it deserves some attention on the part of the research community, and the focus of this attention should lie in collecting empirical evidence to support or refute the assertions proposed in the academic literature on the issue of oral reading. This was one of the main rationales for the research described in this work. The need for conducting the present study also arose from the absence of an empirical investigation examining Hungarian learners’ English reading miscues in Transcarpathian Hungarian schools. Because this topic is not researched in an adequate way, this research is believed to fill the gap. This study was further justified by a desire to explore the application of the technique of analysing learners’ reading miscues in a non-native context.
Використання читання вголос учнями на уроці англійської мови – мікро і макро рівні читання вголос
https://opac3.brff.monguz.hu:443/hu/record/-/record/129751
Keywords: English lesson; micro-and macro levels; reading comprehension; teaching